Leaching of chalcopyrite concentrates

CN116574919BActive Publication Date: 2026-10-27HEBEI GEO UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310655606.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2026-10-27
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

[0004]针对上述存在的环境污染、浸出周期长、浸出率低下以及对设备的要求较高的问题,本公开提供了一种黄铜矿精矿的浸出方法

Benefits of technology

[0015]基于本公开上述实施例的黄铜矿精矿的浸出方法,根据金属锰离子的价态变化特点以及空气中氧气的氧化作用,使得金属锰离子与氧气结合,生成较高价态锰的氧化物,该较高价态锰的氧化物能够与黄铜矿中的硫化铜在含氧氛围下形成耦合状态,强化了制备黄铜矿精矿过程中的氧化环境,提高了对黄铜矿精矿的浸出效率和浸出率。其中添加的卤素盐提供了卤素离子,而黄铜矿中的铜离子存在空轨道,能够与含有孤对电子的卤素离子形成络合离子,进一步提高了铜离子的浸出效率。本公开使用的锰源化合物与卤素盐在含氧的氛围下能够形成协同作用,可实现空气环境下较快速、高效地氧化黄铜矿,提高了黄铜矿的酸浸出的速率和浸出率,不需要进一步加热,就能够在氧化黄铜矿精矿后直接实现酸浸出的过程。同时,锰源化合物和卤素盐在后续的回收利用中较为便捷,在黄铜矿精矿的铜元素湿法冶金方面具有较好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116574919B_ABST
    Figure CN116574919B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a chalcopyrite concentrate leaching method, belonging to the technical field of hydrometallurgy. The chalcopyrite concentrate leaching method comprises: adding a manganese source compound and a halogen salt into pretreated chalcopyrite concentrate, mixing to obtain a mixture, then passing air into the mixture for stirring and grinding treatment to obtain a stirred mixture, then performing acid leaching treatment on the stirred mixture, and finally obtaining leached chalcopyrite concentrate material. The chalcopyrite concentrate material obtained by using the leaching method of the present disclosure further improves the acid leaching efficiency and leaching rate of the chalcopyrite concentrate through the synergistic effect of the added manganese source compound and halogen salt under an oxygen-containing atmosphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of hydrometallurgical technology, and in particular to a leaching method for chalcopyrite concentrate. Background Technology

[0002] Over 70% of copper in nature exists in copper sulfide minerals, with chalcopyrite being one of the main raw materials for smelting and extracting copper metal. Traditional pyrometallurgical processes are the primary method for extracting copper from chalcopyrite, but these processes generate large amounts of SO2 gas, causing severe environmental pollution. While other copper extraction technologies exist, they all suffer from unavoidable problems. For example, microbial leaching of chalcopyrite, while relatively environmentally friendly, suffers from long leaching cycles, low leaching rates, long microbial culture periods, and difficulty in applying it to chalcopyrite concentrates. Atmospheric pressure leaching of chalcopyrite has lower energy consumption, but the oxidants used are often difficult to regenerate. Pressure oxidative acid leaching, while having relatively high leaching rates, is highly corrosive to equipment and places high demands on the equipment.

[0003] Therefore, finding a greener and more efficient enhanced leaching method for chalcopyrite concentrate is key to the development of chalcopyrite smelting technology. Summary of the Invention

[0004] In view of the aforementioned problems of environmental pollution, long leaching cycle, low leaching rate and high equipment requirements, this disclosure provides a leaching method for chalcopyrite concentrate.

[0005] To achieve the above objectives, as one aspect of this disclosure, a leaching method for chalcopyrite concentrate is provided, comprising: adding a manganese source compound, a halogen salt, and water to a pretreated chalcopyrite concentrate and mixing them to obtain a mixture; introducing air into the mixture and performing agitated grinding to obtain a stirred mixture; and subjecting the stirred mixture to acid leaching to obtain a leached chalcopyrite concentrate material.

[0006] According to embodiments of this disclosure, the manganese source compound includes at least one of an inorganic salt of manganese or an oxide of manganese.

[0007] According to embodiments of this disclosure, the halogen salt includes at least one of chloride salts and bromide salts.

[0008] According to embodiments of this disclosure, for every 20g of chalcopyrite concentrate, the amount of halide salt used is 45mg, the amount of manganese element in the manganese source compound is 20-40mg, and the amount of water used is 10-70mL.

[0009] According to embodiments of this disclosure, the stirred grinding conditions are: stirred grinding at 15-25°C for 20-60 min, with an air flow rate of 3-6 L / min.

[0010] According to embodiments of this disclosure, the stirred grinding process also requires the addition of an alkaline solution to make the pH of the mixture > 6.

[0011] According to embodiments of this disclosure, the acid leaching treatment time is 1-5 hours.

[0012] According to embodiments of this disclosure, the pretreated chalcopyrite concentrate is prepared by grinding and pretreating chalcopyrite concentrate. The pretreated chalcopyrite concentrate has a particle size of 0-0.038 μm or 0-0.074 μm and a copper content of 12-30%.

[0013] According to embodiments of this disclosure, the time for stirred grinding is 20-60 minutes.

[0014] According to embodiments of this disclosure, the acidic solution used in the acid leaching treatment includes concentrated sulfuric acid.

[0015] The leaching method for chalcopyrite concentrate based on the above embodiments of this disclosure utilizes the valence state change characteristics of manganese ions and the oxidizing effect of oxygen in the air. This allows manganese ions to combine with oxygen to generate oxides of higher valence manganese. These higher valence manganese oxides can form a coupling state with copper sulfide in chalcopyrite under an oxygen-containing atmosphere, enhancing the oxidizing environment during chalcopyrite concentrate preparation and improving the leaching efficiency and yield. The added halide salt provides halide ions, while copper ions in chalcopyrite possess empty orbitals, enabling them to form complex ions with halide ions containing lone pairs of electrons, further improving the leaching efficiency of copper ions. The manganese source compound and halide salt used in this disclosure can form a synergistic effect under an oxygen-containing atmosphere, achieving rapid and efficient oxidation of chalcopyrite in an air environment. This improves the acid leaching rate and yield of chalcopyrite, allowing for direct acid leaching after chalcopyrite concentrate oxidation without further heating. Meanwhile, manganese source compounds and halogen salts are relatively easy to recycle and reuse, and have good application prospects in the hydrometallurgical processing of copper elements in chalcopyrite concentrate. Attached Figure Description

[0016] The present disclosure will be further described in detail below with reference to the accompanying drawings.

[0017] Figure 1 A flowchart of a method for leaching chalcopyrite concentrate according to an embodiment of this disclosure is shown;

[0018] Figure 2 The X-ray diffraction pattern of chalcopyrite concentrate in Embodiment 1 of this disclosure is shown;

[0019] Figure 3 This diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirring and grinding with the addition of manganese sulfate and sodium chloride in Example 1 of this disclosure.

[0020] Figure 4 The X-ray diffraction pattern of chalcopyrite concentrate in Embodiment 2 of this disclosure is shown;

[0021] Figure 5 This diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirring and grinding with added MnO2 and sodium bromide in Example 2 of this disclosure.

[0022] Figure 6 The X-ray diffraction pattern of chalcopyrite concentrate in Embodiment 3 of this disclosure is shown; and

[0023] Figure 7 The diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirring and grinding with the addition of Mn3O4 and sodium bromide in Example 3 of this disclosure. Detailed Implementation

[0024] To facilitate rapid leaching of chalcopyrite concentrate, related technologies typically involve oxidizing the chalcopyrite to promote a more complete reaction between the copper in the ore and sulfuric acid or other leaching agents. In developing this disclosure, it was discovered that if chalcopyrite can be efficiently oxidized using oxygen from the air under certain conditions, the problems of wet extraction of chalcopyrite concentrate can be partially solved. While pressurized oxidation and acid leaching in related technologies reduce the cost of corrosion-resistant equipment, the process usually requires heating, making it difficult to control.

[0025] Based on this, this disclosure provides a leaching method for chalcopyrite concentrate, which utilizes the characteristics of multi-valence changes of metallic manganese ions in manganese source compounds and the oxidation effect of oxygen in the air, and synergistically utilizes the complexation effect of halide salts containing lone pairs of electrons with copper ions in chalcopyrite. At the same time, the added halide salts can couple with oxides of high-valence manganese, which has an auxiliary strengthening effect on the oxidation of sulfide ores, further improving the leaching rate and leaching efficiency of chalcopyrite concentrate.

[0026] To make the objectives, technical solutions and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments and the accompanying drawings.

[0027] The following illustrative example illustrates a leaching method for chalcopyrite concentrate. It should be noted that this example is merely a specific embodiment of this disclosure and does not limit the scope of protection of this disclosure.

[0028] Figure 1 A flowchart of a method for leaching chalcopyrite concentrate according to an embodiment of this disclosure is shown.

[0029] like Figure 1 As shown, the leaching method for chalcopyrite concentrate includes stages S101-S103.

[0030] In stage S101, manganese source compound, halogen salt and water are added to pretreated chalcopyrite concentrate and mixed to obtain a mixture.

[0031] In stage S102, air is introduced into the mixture for stirring and grinding to obtain a stirred mixture.

[0032] In stage S103, the stirred mixture is subjected to acid leaching to obtain leached chalcopyrite concentrate.

[0033] According to embodiments of this disclosure, the valence state change characteristics of metallic manganese ions and the oxidizing effect of oxygen in the air are utilized to allow metallic manganese ions to combine with oxygen to generate oxides of manganese with a higher valence state. These oxides can form a coupling state with copper sulfide in chalcopyrite under an oxygen-containing atmosphere, thus enhancing the oxidizing environment during the preparation of chalcopyrite concentrate and improving the leaching efficiency and yield. The added halide salt provides halide ions, while copper ions in chalcopyrite have empty orbitals, which can form complex ions with halide ions containing lone pairs of electrons, further improving the leaching efficiency and yield of copper.

[0034] According to embodiments of this disclosure, the pretreated chalcopyrite concentrate is prepared by grinding chalcopyrite concentrate. After pretreatment, the particle size of the chalcopyrite concentrate is 0-0.038 μm or 0-0.074 μm, and the copper content of the chalcopyrite concentrate is 12-30%. During pretreatment, for example, a stirred mill can be used, and the concentration of the slurry is controlled within the range of 20-45%. The grinding pretreatment of the chalcopyrite concentrate is to increase its specific surface area, making it easier for copper sulfide to couple with higher valence manganese ions in an oxygen-containing environment. It also allows for more complete complexation of copper ions with halide ions containing lone pairs of electrons.

[0035] According to embodiments of this disclosure, the manganese source compound includes at least one of inorganic salts of manganese or oxides of manganese. Common valence states of metallic manganese ions include +2, +3, +4, and even higher valence states. Using inorganic salts of manganese and oxides of manganese is more conducive to the combination of metallic manganese ions with oxygen in the air. The manganese source compound can be, for example, manganese sulfate, manganese dioxide, or manganese tetroxide.

[0036] According to embodiments of this disclosure, the halogen salt includes at least one of chloride and bromide salts. The halogen salts used in this disclosure are generally soluble and may be, for example, sodium chloride or sodium bromide. The addition of the halogen salt can form a complex with copper ions, and the halogen salt can couple with high-valence manganese oxides under oxygen-containing conditions, thus providing an auxiliary strengthening effect on the oxidation of sulfide ores.

[0037] According to embodiments of this disclosure, for every 20g of chalcopyrite concentrate, the amount of halide salt used is 45mg. The halide salt can be added in solution form, with a concentration of 3-30g / L. Preliminary experiments related to this disclosure revealed that when the amount and concentration of halide salt are controlled appropriately, the leaching effect of the chalcopyrite concentrate is better.

[0038] According to embodiments of this disclosure, for every 20g of chalcopyrite concentrate, the amount of manganese in the manganese source compound is 20-40mg, for example, 20mg, 25mg, 30mg, 35mg, 40mg, etc. When the amount of manganese source compound is controlled at an appropriate level, the leaching effect of the obtained chalcopyrite concentrate is better.

[0039] According to embodiments of this disclosure, the stirred grinding conditions are as follows: stirred grinding at 15-25°C for 20-120 minutes, with an air flow rate of 3-6 L / min. In related technologies, acid leaching of chalcopyrite concentrate typically employs heating or pressurization, which places high demands on the reaction conditions and equipment used. In contrast, this disclosure only requires the introduction of air to achieve an oxidizing atmosphere. Compared to heating or pressurization, this method causes relatively less corrosion to the reactor, simplifies the process, and further improves the durability of the equipment.

[0040] Furthermore, the stirring grinding time is 20-60 minutes.

[0041] According to embodiments of this disclosure, the stirred grinding process also requires the addition of an alkaline solution to bring the pH of the mixture to >6. The alkaline solution used can be, for example, lime or sodium hydroxide, preferably lime, which is relatively inexpensive and suitable for large-scale engineering preparation processes.

[0042] According to embodiments of this disclosure, the acidic solution used in the acid leaching treatment includes concentrated sulfuric acid. During preliminary experiments related to this disclosure, it was found that concentrated sulfuric acid resulted in higher leaching efficiency; when dilute sulfuric acid or other acids were used, the leaching time of the chalcopyrite concentrate needed to be further extended; and when ammonia, hydrochloric acid, or other leaching agents were used, it was necessary to adjust suitable parameters such as the stirring and grinding time and the leaching time. Sulfuric acid was preferred, as it facilitated subsequent electrolytic copper production.

[0043] According to embodiments of this disclosure, the acid leaching treatment time is 1-5 hours. The duration of the acid leaching treatment depends primarily on the concentration of the acidic solution used.

[0044] Furthermore, the manganese source compound used in this disclosure can form a synergistic effect with the halogen salt in an oxygen-containing atmosphere, which can achieve faster and more efficient oxidation of chalcopyrite in an air environment, further improving the acid leaching rate and leaching efficiency of chalcopyrite concentrate, and enabling the acid leaching process to be directly realized after oxidizing chalcopyrite concentrate.

[0045] Specifically, manganese source compounds such as manganese sulfate, manganese dioxide, and manganese tetroxide, as well as halide salts represented by sodium chloride and sodium bromide, have the advantages of low price, stable properties, and wide availability. Among these, manganese source compounds utilize the changing valence state of manganese ions to enhance the oxidizing environment during stirred grinding. Furthermore, manganese source compounds and halide salts can be recovered and reused in subsequent hydrometallurgical processes, showing promising application prospects in the hydrometallurgical processing of copper elements in chalcopyrite concentrate.

[0046] It should be noted that while the heating and pressurization methods used in related technologies can process low-grade chalcopyrite, chalcopyrite concentrate requires a relatively long reaction time, typically exceeding four hours, due to the large amount of sulfides that need to be oxidized. Preliminary experiments conducted in this disclosure revealed that directly introducing oxygen into the chalcopyrite concentrate with only halogen salts and no manganese source compound yielded unsatisfactory results. This is primarily because oxygen has low solubility in solution, leading to a prolonged oxidation reaction and low oxygen utilization efficiency. This disclosure utilizes a synergistic leaching process of manganese source compound and halogen salt in a stirred mill. The manganese ions in the manganese source compound enhance the efficiency of oxygen participation in the oxidation of chalcopyrite in solution, while the combination of halide ions and manganese ions further improves the oxidation efficiency of the chalcopyrite concentrate.

[0047] The present disclosure is further illustrated below by way of proportions, embodiments, accompanying drawings, and related test experiments and results. In the following detailed description, numerous specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Moreover, the details in the following embodiments can be arbitrarily combined to form other feasible embodiments without conflict.

[0048] It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of this disclosure is not limited thereto. The chemicals and raw materials used in the following embodiments are all commercially available or prepared in-house using recognized methods.

[0049] Example 1

[0050] Leaching methods for chalcopyrite concentrate include:

[0051] Chalcopyrite concentrate with a copper content of approximately 15% was ground to a particle size of 0.038 μm. After completing the pretreatment process, 20 g of the pretreated chalcopyrite concentrate was added to a stirred mill, along with 10 ml of water and 10 ml of a 20 g / L solution containing Mn. 2+ A manganese sulfate solution was prepared, and 5 ml of a 9 g / L sodium chloride solution was added. The mixture was stirred and ground to obtain a mixture.

[0052] At 15°C, air was introduced at a rate of 6 L / min and the mixture was stirred and ground. 5 ml of 4 g / L lime slurry was added in batches to maintain a pH > 6. The stirring and grinding process was continued for 20 minutes. After the stirring and grinding was completed, the slurry was removed, and 5 ml of 98% concentrated sulfuric acid was added directly for acid leaching for 1 hour.

[0053] It should be noted that the chalcopyrite concentrate used in this Example 1 was taken from a copper mine in Chengde City, Hebei Province. It is mainly low-grade chalcopyrite concentrate, which was pre-processed by artificial grinding to below 0.038μm. Figure 2 The X-ray diffraction pattern of the chalcopyrite concentrate in Embodiment 1 of this disclosure is shown. Prior to the experiment in Embodiment 1, XRD analysis was performed on the low-grade chalcopyrite concentrate using an X-ray diffraction system. The analysis revealed that the main phases of the low-grade chalcopyrite concentrate were pyrite and chalcopyrite. The XRD analysis results are as follows: Figure 2 As shown.

[0054] The leaching effect of the chalcopyrite concentrate obtained in Example 1 was tested, and the specific test process and results are shown below.

[0055] Under the same experimental conditions, the control group without any added substances was used as the blank test, and the control group was compared with the one containing 10 ml of 20 g / L Mn. 2+ The leaching effect before and after adding 5 ml of 9 g / L sodium chloride solution to manganese sulfate solution. Figure 3 This diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirred grinding with the addition of manganese sulfate solution and sodium chloride solution in Example 1 of this disclosure. Figure 3 The results show that in the blank test without any additives, the copper leaching rate in the chalcopyrite concentrate was only 26.72%. When 10 ml of 20 g / L Mn was added... 2+ After leaching with manganese sulfate solution and 5 ml of 9 g / L sodium chloride solution, the copper leaching rate in chalcopyrite concentrate reached 98.13%. This demonstrates that combining manganese source compounds with halogen salts can effectively utilize oxygen from the air to directly oxidize chalcopyrite during stirred grinding, achieving a highly efficient leaching result for the chalcopyrite concentrate.

[0056] Example 2

[0057] Leaching methods for chalcopyrite concentrate include:

[0058] Chalcopyrite concentrate with a copper content of approximately 30% was ground to a particle size of 0.074 μm. After completing the pretreatment process of the chalcopyrite concentrate, 20 g of the pretreated chalcopyrite concentrate was added to a stirred mill, along with 10 ml of water, 70 ml of water, and 4.5 g of solid MnO2 (equivalent to adding 70 ml of 40 g / L MnO2). 2+ (A manganese sulfate solution) was added, and 5 ml of a 9 g / L sodium bromide solution was added. The mixture was stirred and ground to obtain a mixture.

[0059] At 15°C, air was introduced at a rate of 6 L / min and stirred grinding was performed. 5 ml of 4 g / L lime slurry was added in batches to maintain the pH above 6. Stirring and grinding was continued for 60 minutes. After stirring and grinding, the slurry was extracted, and 5 ml of 98% concentrated sulfuric acid was added directly for acid leaching for 1 hour.

[0060] It should be noted that the chalcopyrite concentrate used in this Example 2 was taken from a copper mine in Guizhou Province. It is mainly a high-grade chalcopyrite concentrate, which was pre-processed by artificial grinding to below 0.074μm. Figure 4 The X-ray diffraction pattern of the chalcopyrite concentrate used in Example 2 is shown. Before conducting the experiment in Example 2, XRD analysis was performed on the high-grade chalcopyrite concentrate using an X-ray diffraction system. The analysis revealed that the main phase composition of the high-grade chalcopyrite concentrate was chalcopyrite. The XRD analysis results are shown below. Figure 4 As shown.

[0061] The leaching effect of the chalcopyrite concentrate obtained in Example 2 was tested, and the specific test process and results are shown below.

[0062] Under the same experimental conditions, a blank control group without any added substances was used to compare the leaching effects before and after adding a mixture of 70 ml water and 4.5 g MnO2. Figure 5 This diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirred grinding with the addition of MnO2 and sodium bromide in Example 2 of this disclosure. Figure 5 The results show that in the blank test without any additives, the copper leaching rate in chalcopyrite concentrate was only 35.56%. However, after adding a solution of 70 ml water and 4.5 g MnO2, and 5 ml of a 9 g / L sodium bromide solution, the copper leaching rate in chalcopyrite concentrate reached 96.82%.

[0063] Example 3

[0064] Leaching methods for chalcopyrite concentrate include:

[0065] Chalcopyrite concentrate with a copper content of approximately 24% was ground to a particle size of 0.074 μm. After completing the pretreatment process of the chalcopyrite concentrate, 20 g of the pretreated chalcopyrite concentrate was added to a stirred mill, along with 10 ml of water, 20 ml of water, and 1 g of Mn3O4 (equivalent to adding 20 ml of 40 g / L Mn3O4). 2+ (A manganese sulfate solution) was added, and 5 ml of a 9 g / L sodium bromide solution was added. The mixture was stirred and ground to obtain a mixture.

[0066] At 15°C, air was introduced at a rate of 6 L / min and stirred grinding was performed. 5 ml of 4 g / L lime slurry was added in batches to maintain a pH > 6. Stirring and grinding were continued for 45 minutes. After stirring and grinding, the slurry was extracted, and 5 ml of 98% concentrated sulfuric acid was added directly for acid leaching for 1 hour.

[0067] It should be noted that the chalcopyrite concentrate used in this embodiment 3 was taken from a copper mine in Daye, Hubei Province. It is mainly a high-grade chalcopyrite concentrate, which was pre-processed by artificial grinding to below 0.074μm. Figure 6 The X-ray diffraction pattern of the chalcopyrite concentrate in Embodiment 3 of this disclosure is shown. Before conducting the experiment in Embodiment 3, XRD analysis was performed on the high-grade chalcopyrite concentrate used. The analysis revealed that the main phase composition of the high-grade chalcopyrite concentrate was chalcopyrite. The XRD analysis results are as follows: Figure 6 As shown.

[0068] The leaching effect of the chalcopyrite concentrate obtained in Example 3 was tested, and the specific test process and results are shown below.

[0069] Under the same experimental conditions, a blank control group without any added substances was used to compare the leaching effects before and after adding a mixture of 20 ml of water and 1 g of Mn3O4. Figure 7 This diagram illustrates the results of a blank experiment and the leaching of chalcopyrite concentrate after stirred grinding with added Mn3O4 solution and sodium bromide solution in Example 3 of this disclosure. Figure 7 The results show that in the blank test without any additives, the copper leaching rate in chalcopyrite concentrate was only 32.35%. However, after adding 20 ml of a mixture of water and 1 g of Mn3O4, and 5 ml of a 9 g / L sodium bromide solution, the copper leaching rate in chalcopyrite concentrate reached 97.24%.

[0070] Comparative Example 1

[0071] The chalcopyrite concentrate used in Comparative Example 1 was obtained from a copper mine in Daye, Hubei Province. It is mainly high-grade chalcopyrite concentrate, which was pre-processed by artificial grinding to below 0.074 μm.

[0072] Chalcopyrite concentrate with a copper content of about 24% was ground to a particle size of 0.074 μm. After the pretreatment process of chalcopyrite concentrate was completed, 20 g of the pretreated chalcopyrite concentrate was added to a stirred mill, along with 10 ml of water, 20 ml of water and 1 g of Mn3O4 (equivalent to adding 20 ml of 40 g / L Mn2+ manganese sulfate solution), and stirred milling was carried out to obtain a mixture.

[0073] At 15°C, air was introduced at a rate of 6 L / min and stirred grinding was performed. 5 ml of 4 g / L lime slurry was added in batches to maintain a pH > 6. Stirring and grinding were continued for 45 minutes. After stirring and grinding, the slurry was extracted, and 5 ml of 98% concentrated sulfuric acid was added directly for acid leaching for 1 hour.

[0074] The leaching effect of the chalcopyrite concentrate obtained in Comparative Example 1 was tested. The specific test process and results are shown below.

[0075] Using a blank control group (without any added substances), the leaching effects before and after adding a mixture of 20 ml water and 1 g Mn3O4 were compared. In the blank test without any added substances, the copper leaching rate in the chalcopyrite concentrate was only 32.35%, while the copper leaching rate in the mixture with 20 ml water and 1 g Mn3O4 added reached only 74.24%.

[0076] In summary, the method disclosed herein is applicable to various types and specifications of chalcopyrite crude materials. Moreover, the preparation process is relatively green and efficient, and the process used is simple and incurs low costs. The manganese source compound and halogen salt used in this disclosure are added to an aerated stirred mill, which enables the chalcopyrite concentrate to be rapidly oxidized by oxygen in the air at room temperature and pressure, thereby leaching it subsequently. This is of great significance for the industrial leaching of chalcopyrite concentrate.

[0077] While several embodiments have been provided in this disclosure, those skilled in the art should understand that changes can be made to the embodiments herein without departing from the spirit of this disclosure. The above embodiments are merely exemplary and should not be construed as limiting the scope of this disclosure.

[0078] The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of this disclosure. It should be understood that the above descriptions are merely specific embodiments of this disclosure and are not intended to limit this disclosure. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the protection scope of this disclosure.

Claims

1. A leaching method for chalcopyrite concentrate, comprising: Manganese source compound, halogen salt and water are added to pretreated chalcopyrite concentrate and mixed to obtain a mixture; Air is introduced into the mixture for stirring and grinding, and alkali solution is added to make the pH of the mixture > 6, resulting in a stirred mixture. The stirred mixture is subjected to acid leaching to obtain leached chalcopyrite concentrate; wherein the manganese source compound includes inorganic salts of manganese; and the halogen salt includes at least one of chloride salts and bromide salts. The conditions for stirred grinding are as follows: Stirred grinding is carried out at a temperature of 15-25℃ for 20-120 minutes, with an air flow rate of 3-6 L / min. For every 20g of chalcopyrite concentrate, the amount of the halogen salt is 45mg, the amount of manganese in the manganese source compound is 20-40mg, and the amount of water is 10-70mL; the acid leaching time is 1-5h.

2. The method according to claim 1, wherein, The pretreated chalcopyrite concentrate is prepared by grinding and pretreating chalcopyrite concentrate. After pretreatment, the particle size of the chalcopyrite concentrate is 0-0.074μm and is not zero. The copper content of the chalcopyrite concentrate is 12-30%.

3. The method according to claim 1, wherein, The time for stirred grinding is 20-60 minutes.

4. The method according to claim 1 or 3, wherein the acidic solution used in the acid leaching treatment includes sulfuric acid.

Citation Information

Patent Citations

  • Method for leaching copper sulfide ore

    JP2013185236A